2005
DOI: 10.1007/s11661-005-0059-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melt temperature and casting speed on the structure and defect formation during direct-chill casting of an Al-Cu alloy

Abstract: A thorough experimental investigation of the effects of melt temperature and casting speed on the structure and defect formation during the steady and nonsteady stages of direct-chill (DC) casting of an Al-2.8 pct Cu alloy is performed. In addition, the temperature and melt-flow distributions in the sump of billets cast at different melt temperatures are numerically simulated and used in the discussion on the experimental results. Apart from already known phenomena such as the coarsening of the structure, deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 16 publications
3
77
1
Order By: Relevance
“…Computer simulations of directchill casting confirm that the increase in melt temperature deepens the sump (region 1 + 2, see Fig. 2a) and narrows the transition region (region 2) by shifting both the liquidus and the solidus isotherms downwards [25,33]. But liquidus position is affected to a greater extent.…”
Section: Effect Of DC Casting Process Parametersmentioning
confidence: 76%
“…Computer simulations of directchill casting confirm that the increase in melt temperature deepens the sump (region 1 + 2, see Fig. 2a) and narrows the transition region (region 2) by shifting both the liquidus and the solidus isotherms downwards [25,33]. But liquidus position is affected to a greater extent.…”
Section: Effect Of DC Casting Process Parametersmentioning
confidence: 76%
“…They also affirm that the porosity of the solid-state metal occurs due to the liquid incapacity to fill the bubbles during the metal continuous cooling and solidification (the volume shrinkage associated with solidification cannot be compensated by the interdendritic flowing opposite to the displacement of the isotherms). All those variables affect the amount, size and morphology of formed pores [1][2][3][4][5][6][7] . Gali…”
Section: Methodsmentioning
confidence: 99%
“…Some studies about the Direct Chill process showed that, the melt temperature and casting speed have a great influence on solid macrossegregation and on billet porosity [1][2][3] . The porosity of the obtained solid-state metal has a strong influence on subsequent forming process, especially on aluminum alloy rolling.…”
Section: Introductionmentioning
confidence: 99%
“…These are provoked by higher energy extraction rates at the water impingement point to keep the system under equilibrium. Faster casting velocities require a corresponding hike in heat flux, as more heat is removed from the ingot [21,22].…”
Section: Casting Velocitymentioning
confidence: 99%